2023
DOI: 10.1002/gps.5973
|View full text |Cite
|
Sign up to set email alerts
|

Improving older adults' autobiographical memory through video‐conferencing intervention during COVID‐19

Abstract: BackgroundAutobiographical memory (AM) is valuable not only as an indicator of mental health and cognitive function, but also as a target of therapeutic intervention for older adults. In the context of the COVID‐19 pandemic, the demand for online psychosocial interventions and assessment services has sharply increased. Thus, the present study examined the effectiveness of videoconferencing AM (vAM) intervention using the Ecological Momentary Assessment (EMA) method in addition to the traditional paper‐and‐penc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This work has shown, for example, that individuals recruited through MTurk can report on their autobiographical memories in an unsupervised context, and they experience positive and negative memories similar to in the laboratory (Gower et al, 2023). In addition, several studies have demonstrated that autobiographical memory training programs, developed in the laboratory and clinic, can be delivered virtually in a videoconference format (Jung et al, 2023;. Beyond autobiographical memory, recent research has in fact shown that many cognitive tasks, despite the reduction in control and translation to a home environment, produce similar outcomes when administered by videoconference (Brearly et al, 2017;Marra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This work has shown, for example, that individuals recruited through MTurk can report on their autobiographical memories in an unsupervised context, and they experience positive and negative memories similar to in the laboratory (Gower et al, 2023). In addition, several studies have demonstrated that autobiographical memory training programs, developed in the laboratory and clinic, can be delivered virtually in a videoconference format (Jung et al, 2023;. Beyond autobiographical memory, recent research has in fact shown that many cognitive tasks, despite the reduction in control and translation to a home environment, produce similar outcomes when administered by videoconference (Brearly et al, 2017;Marra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%